2020
DOI: 10.1186/s13195-020-00587-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of amyloid PET measured in Centiloid units with neuropathological findings in Alzheimer’s disease

Abstract: Background: The Centiloid scale was developed to standardise the results of beta-amyloid (Aβ) PET. We aimed to determine the Centiloid unit (CL) thresholds for CERAD sparse and moderate-density neuritic plaques, Alzheimer's disease neuropathologic change (ADNC) score of intermediate or high probability of Alzheimer's Disease (AD), final clinicopathological diagnosis of AD, and expert visual read of a positive Aβ PET scan. Methods: Aβ PET results in CL for 49 subjects were compared with post-mortem findings, vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 37 publications
(64 reference statements)
8
99
2
1
Order By: Relevance
“…The 12 CL cut‐off was previously proposed to detect subtle Aβ pathology in a comparison against CSF Aβ42 and neuropathological assessment of Aβ plaques (La Joie et al , 2019; Salvadó et al , 2019). In contrast, 30 CL is a cut‐off that is in the range of agreement with the visual read method in clinical populations (24–35 CL) and therefore reflects established Aβ pathology (Leuzy et al , 2016; Rowe et al , 2017; La Joie et al , 2019; Salvadó et al , 2019; Amadoru et al , 2020). We observed that all CSF and plasma p‐tau biomarkers were increased in the group of participants with CL > 30 with respect to the negative group (CL ≤ 12; Fig 3K–O).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 CL cut‐off was previously proposed to detect subtle Aβ pathology in a comparison against CSF Aβ42 and neuropathological assessment of Aβ plaques (La Joie et al , 2019; Salvadó et al , 2019). In contrast, 30 CL is a cut‐off that is in the range of agreement with the visual read method in clinical populations (24–35 CL) and therefore reflects established Aβ pathology (Leuzy et al , 2016; Rowe et al , 2017; La Joie et al , 2019; Salvadó et al , 2019; Amadoru et al , 2020). We observed that all CSF and plasma p‐tau biomarkers were increased in the group of participants with CL > 30 with respect to the negative group (CL ≤ 12; Fig 3K–O).…”
Section: Resultsmentioning
confidence: 99%
“…To note, the cut‐off used here for CSF Aβ42/40 has been optimized to detect preclinical Alzheimer and is higher (and thus more sensitive) than cut‐offs with high specificity usually used for diagnostic purposes in symptomatic AD (Milà‐Alomà et al , 2020). Likewise, we used the cut‐off of CL > 12 (Salvadó et al , 2019), which reflects very mild Aβ changes, and it is considerably lower than the CL values found when Aβ pathology is well‐established in symptomatic AD (Leuzy et al , 2016; Rowe et al , 2017; La Joie et al , 2019; Salvadó et al , 2019; Amadoru et al , 2020). Even with these very early cut‐offs, we were able to detect significant changes in these novel CSF p‐tau biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this same PET autopsy study [ 18 ] as well as in a previous report [ 26 ], a higher threshold (Centiloid = 24) was observed against intermediate to high levels of AD neuropathological changes including thus both Aβ and tau lesions as a gold standard (unlike CERAD plaque count), which may be closer to a dementia endpoint. A recent paper observed that a Centiloid threshold = 21 detected moderate or frequent plaque density while Centiloid = 10 was optimal for excluding neuritic plaques [ 27 ]. They also observed higher threshold (Centiloid = 49) against intermediate to high levels of AD neuropathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate amyloid burden was defined as CL values between 20 and 50 and high amyloid burden as CL ≥ 50 [ 23 ]. Twenty-two (14%) CN participants showed intermediate amyloid burden (CL range 22.2–47.8), while eight (5%) showed high amyloid burden (CL range 66.25–184.9).…”
Section: Methodsmentioning
confidence: 99%